Analysis of the Influencing Factors of Enterprise Environmental Ethics on Enterprise Economic Performance - Yufang Jiang; Xujie Lyu (Discrete Dynamics in Nature and Society)
In the information age, people’s awareness of living environmental protection has increased unprecedentedly, and the concept of green environmental protection in enterprise economic behavior has been paid more and more attention by the market and consumers. The integration of green ideas, the improvement of production technology, and the research and development of environmental protection products have become the development trend of enterprises, and environmental ethical responsibility has also become an inevitable problem for enterprises. This paper analyzes the impact of enterprises’ conscious commitment to environmental ethics on their economic benefits, identifies the key influencing factors with the help of scientific statistical methods, analyzes the action mechanism of influencing factors in performance on the basis of the effect model and communication model, and analyzes the correlation between environmental ethics and economic benefits. The experimental results show that the long-term dissemination of innovation and reputation factors in environmental ethics is conducive to the dissemination of green innovative technologies and products, obtaining the attention and recognition of more enterprises and stakeholders, broadening the scope of cooperation and sales, and obtaining the support of German consumers. Environmental ethics has a short-term direct effect on performance. When the direct effect is reduced, the intermediary effect of innovation and reputation factors can achieve a positive effect on performance by transmitting benefits.